2014
DOI: 10.1021/ja503590h
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Structures and Gram Scale Synthesis of Three Tetrahedral Quantum Dots

Abstract: Luminescent semiconducting quantum dots (QDs) are central to emerging technologies that range from tissue imaging to solid-state lighting. However, existing samples are heterogeneous, which has prevented atomic-resolution determination of their structures and obscured the relationship between their atomic and electronic structures. Here we report the synthesis, isolation, and structural characterization of three cadmium selenide QDs with uniform compositions (Cd35Se20(X)30(L)30, Cd56Se35(X)42(L)42, Cd84Se56(X)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
383
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(446 citation statements)
references
References 50 publications
31
383
4
Order By: Relevance
“…These structures have been highly useful in the analysis of preferred ligand binding on QD facets, but unfortunately high-resolution crystal structures have yet to be generated for larger clusters (>2 nm) that are more commonly used, or for more diverse shapes and ligand types. Interestingly, other magic-sized clusters have been reported that seem to be distinct, either synthesized with X-type ligands to yield cadmium-rich QDs [79], or synthesized with excess L-type amines to yield neutral QDs (e.g. Cd 33 Se 33 ) [69, 70].…”
Section: Quantum Dot Ligand Coordinationmentioning
confidence: 99%
“…These structures have been highly useful in the analysis of preferred ligand binding on QD facets, but unfortunately high-resolution crystal structures have yet to be generated for larger clusters (>2 nm) that are more commonly used, or for more diverse shapes and ligand types. Interestingly, other magic-sized clusters have been reported that seem to be distinct, either synthesized with X-type ligands to yield cadmium-rich QDs [79], or synthesized with excess L-type amines to yield neutral QDs (e.g. Cd 33 Se 33 ) [69, 70].…”
Section: Quantum Dot Ligand Coordinationmentioning
confidence: 99%
“…Very recently, low temperature, nonphosphinated methods for synthesis of ultrasmall CdSe nanocrystals were reported. [30][31] In order to address the current challenges of understanding the formation mechanism of semiconductor nanocrystals, we have investigated here the formation of ~1.6 nm CdSe nanocrystals using a new Se precursor (Scheme 1) prepared from a reaction between elemental selenium and 1-octadecene (ODE) requiring 1-hexanethiol (HT), which will be heretofore referred to as Se-ODE-HT. From 77 Se and 1 H NMR, and MS characterizations, we identify this Se-ODE-HT precursor as a new Se-bridged organic species that can be used in CdSe nanocrystals synthesis as the reactive Se precursor.…”
Section: Introductionmentioning
confidence: 99%
“…A number of synthetic approaches have been documented that typically involved a laborious trial-and-error scheme to produce colloidal semiconductor CdTe (refs 31, 32, 33, 34), CdSe (refs 34, 35, 36, 37, 38, 39, 40, 41, 42), CdS (refs 43, 44) and other composition MSCs45464748. These studies did not address the formation pathway of the MSCs, although some did propose that the MSCs were the actual nuclei for the growth of NCs13384347.…”
mentioning
confidence: 99%
“…However, the coexistence of MSCs of several sizes (instead of a single size) with a single CdE RQD ensemble in one reaction batch does not support such an assumption3446. In addition to the synthetic procedures, there is limited information on MSCs obtained from mass measurements354148, energy calculations35 and structural characterizations by X-ray diffraction42. Even with these investigations, in hand there remains much to discuss about the results3542.…”
mentioning
confidence: 99%
See 1 more Smart Citation